The effect of ultrasonic surface rolling process on the fretting fatigue property of GH4169 superalloy - Yang, Jing; Liu, Daoxin; Zhang, Xiaohua; Liu, Mingxia; Zhao, Weidong; Liu, Chengsong (International journal of fatigue, 2020)
•The fretting fatigue performance is significantly improved by USRP treatment.•The gradient nanostructure is formed on the surface of USRP sample.•The equiaxial nanograins are synthetic on the top surface of USRP-3.•Compressive residual stress plays a paramount role in improving FF of GH4169.•The mechanism on FF of GH4169 superalloy is revealed. To improve the fretting fatigue (FF) resistance of GH4169 superalloy, ultrasonic surface rolling process (USRP) is carried once and three times on material surface and the effect of surface integrity on FF is investigated. The results show that USRP significantly reduces the surface roughness of GH4169 superalloy and improves surface micro-hardness as well as induces a high intensity compressive residual stress at deep thickness. The dislocation density beneath the top surface is increased and the grains of the material surface are refined. A gradient nanostructured layer is observed beneath the surface and the equiaxed nanograins are generated with the size of around 37.6 nm at the top surface of USRP-3 sample. The FF test indicates the FF life of GH4169 superalloy increase by 3.6 times and 11 times, by one and three USRP treatments, respectively. In addition, the factor separation test indicates that the compressive residual stress plays an important role in improving the FF life of GH4169 superalloy.